Polymorphism of the ApoE locus in the Azores Islands (Portugal) - Bettencourt, Conceição (2006)
The aim of this work was to report on the polymorphism of the ApoE locus in the Azores Islands (Portugal) in order to get insights on the genetic background that influences the lipid profile in this population, ascertained as considerably high in a preliminary study of a sample of healthy subjects (60% of individuals were hypercholesterolemics). One hundred and twenty six Azorean individuals were typed for ApoE polymorphism using standard PCR-RFLP. The allelic frequencies obtained for ε2, ε3 and ε4 were 6.75%, 83.73% and 9.52%, respectively. Genotypic frequencies were in conformity with Hardy-Weinberg expectations. The ε3/ε3 genotype presented the highest frequency (69.84%), whilst ε4/ε4 was the least frequent (0.79%). The genotypic and allelic frequencies observed were similar to those reported for other Iberian samples. Furthermore, Nei’s gene diversity (0.2864±0.0351) was similar to the reported for samples from Mainland Portugal. Results obtained did not evidence a particular behaviour of the ApoE locus that could be directly related with the high levels of total cholesterol determined in the Azorean population.